2019
DOI: 10.3390/cells8121496
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes as A New Therapeutic Target in Schizophrenia: From Histopathological Findings to Neuron-Oligodendrocyte Interaction

Abstract: Imaging and postmortem studies have revealed disturbed oligodendroglia-related processes in patients with schizophrenia and provided much evidence for disturbed myelination, irregular gene expression, and altered numbers of oligodendrocytes in the brains of schizophrenia patients. Oligodendrocyte deficits in schizophrenia might be a result of failed maturation and disturbed regeneration and may underlie the cognitive deficits of the disease, which are strongly associated with impaired long-term outcome. Cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 112 publications
(155 reference statements)
1
41
0
Order By: Relevance
“…In the present study we found dystrophic changes but no degeneration of oligodendrocytes in layer 5 of the PFC in schizophrenia. Thus, a prominent deficit of oligodendrocytes in layer 5 of the PFC cannot be explained by current oligodendrocyte degeneration, it may be the result of disrupted maturation and proliferation of oligodendrocyte progenitors in schizophrenia (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we found dystrophic changes but no degeneration of oligodendrocytes in layer 5 of the PFC in schizophrenia. Thus, a prominent deficit of oligodendrocytes in layer 5 of the PFC cannot be explained by current oligodendrocyte degeneration, it may be the result of disrupted maturation and proliferation of oligodendrocyte progenitors in schizophrenia (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…A widely accepted hypothesis for the origin of schizophrenia is that variations in several risk genes interact with environmental stimuli, affecting brain development and function, leading to abnormal information processing by the brain 1,2,14 . Studies have associated the development and establishment of schizophrenia with dysfunctions in neurotransmitter systems and oligodendrocytes 15,16 . Oligodendrocytes are cells that wrap around axons in specialized layers of cell membrane to form the myelin sheath.…”
mentioning
confidence: 99%
“…Neuropathological and neuroimaging studies have also found abnormalities and degeneration related to OLs, especially in the frontal and temporal lobes and in the corpus callosum of schizophrenia patients 21 . Moreover, studies have suggested that oligodendrocytes may be a target of antipsychotics 16,21,22 . Thus, studying the effects of these drugs on oligodendrocytes may contribute to the improvement of current treatments and to the development of new therapeutic approaches.…”
mentioning
confidence: 99%
“…Moreover, an oligodendrocyte deficit can cause impaired myelination with a subsequent lack of nerve impulse transmission and cognitive impairment related to SCZ. It has also been hypothesized that inflammation in the brain along with microglia overactivity is involved in oligodendrocyte dysfunction (Raabe et al 2018(Raabe et al , 2019.…”
Section: Recent Issuesmentioning
confidence: 99%
“…(1) cells from tissues other than the brain may sometimes be contaminated, (2) due to different embryonal origins, microglia cannot be included in almost all of the iPSC cellderived brain models and (3) conditions arising from longlasting processes such as aging and maturation are difficult to reproduce when using brain organoids (Quadrato et al 2016;Raabe et al 2018Raabe et al , 2019.…”
Section: Recent Issuesmentioning
confidence: 99%